Poemas, Encruzilhadas e Vozes Insubmissas: o escreviver de mulher preta como estilhaçamento das amarras coloniais (Simbiótica. Revista Eletrônica, 2023)
We ask for permission to share pain, struggles and healing processes chanted in current words, deep, enchanted, incarnate and Afro pindoramic words of many black women in me. The poems here express cries of revolt and healing processes. Marginal poetry is a place of healing for us black women, it is part of our self-recognition as a black person, as a black woman and terreiro. As I asserted myself in a society of pain, it was in the strength of the enchanted ones that I crossed my body with the strength of many ancestors, a continuous trance with my guides, at the crossroads and encounter of an insurgent subjectivity, of many people in me. The poems shared here are cries of freedom that express and inscribe a black woman in the political struggle against racism. Words are populated by people and enchanted. The poems are about us, people incarnate of a living nature.